2013
DOI: 10.3897/compcytogen.v7i4.6075
|View full text |Cite
|
Sign up to set email alerts
|

Cytological investigations and new chromosome number reports in yarrow (Achillea millefolium Linnaeus, 1753) accessions from Iran

Abstract: In this study, a new chromosome number for Iranian yarrow (Achillea millefolium L.) accessions was reported. Cytological analyses on four Achillea millefolium accessions, indicated that two accessions were diploids (2n=2x=18) and two tetraploids (2n=4x=36). Cluster analysis based on chromosomal characteristics and karyotype asymmetry, categorized the four accessions separated into two groups. In terms of the Stebbins’ system, the karyotype of diploid accessions grouped in 2A class. The average value of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 23 publications
7
10
0
Order By: Relevance
“…Accordingly, a range between diploid to hexaploid has been reported for Ac.aleppica species (Chehregani & Javaheri, 2014); however, all the accessions of the species were diploid in the present study. The tetraploid level was reported for A. bieberestini species (Afshari et al, 2013), which was consistent with the present results Afshari and et al, reported diploid and tetraploid levels for Ac.millefolium species (Afshari et al, 2013). In another study, Hexa and Octa-ploidy levels were reported for the species (Ebrahim et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Accordingly, a range between diploid to hexaploid has been reported for Ac.aleppica species (Chehregani & Javaheri, 2014); however, all the accessions of the species were diploid in the present study. The tetraploid level was reported for A. bieberestini species (Afshari et al, 2013), which was consistent with the present results Afshari and et al, reported diploid and tetraploid levels for Ac.millefolium species (Afshari et al, 2013). In another study, Hexa and Octa-ploidy levels were reported for the species (Ebrahim et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the evolution and speciation of the genus was through intra-chromosomal asymmetry rather than increasing or decreasing the chromatin content and chromosome length. The average length of each chromosome ranged from 2.93 to 3.55 microns for the species, which was consistent with other reports (Afshari et al, 2013;Sahin et al, 2006). Meanwhile, the chromosome length range was higher in certain reports than that in the results of the present study, and longer chromosomes were reported for the species (Aksu et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations